Comparative Study of Restorative Justice in Indonesia and Australia under The New Criminal Code - Agnes Zefanya Sinaga; Indung Wijayanto (Universitas Negeri Semarang, 2026)
In addition to analyzing the role of victims in the process, this study compares the implementation of restorative justice in Indonesia's New Criminal Code (KUHP) with developing practices in Australia. Using a legislative and comparative law perspective, this study uses a normative legal technique. According to research, Law No. 1 of 2023's restorative justice measures represent a paradigm change from a retributive to a restorative approach. Nevertheless, these clauses are still mostly normative and lack thorough implementation methods. Australia, on the other hand, has created a restorative justice system that is more integrated and structured, giving victims greater chances to participate in the case settlement process. According to this study, victims play a more active and significant role in Australia, but in Indonesia, their position is still relatively limited because there are no specific regulations. A careful examination also identifies implementation issues, including ambiguous standards, possible discrepancies in application, and constraints on the ability of law enforcement personnel. Additionally, the implementation of restorative justice has strategic implications for advancing the global agenda established by the United Nations through the Sustainable Development Goals (SDGs), especially Goal 16 on justice, peace, and institutional building. Therefore, in order to guarantee the successful implementation of restorative justice in Indonesia while assisting in the development of a just and sustainable judicial system, it is required to strengthen subsidiary rules, institutions, and human resource capability.